2008
DOI: 10.1093/toxsci/kfm313
|View full text |Cite
|
Sign up to set email alerts
|

Toxicogenomic Analysis of Gender, Chemical, and Dose Effects in Livers of TCDD- or Aroclor 1254–Exposed Rats Using a Multifactor Linear Model

Abstract: Chronic exposure of Sprague-Dawley (SD) rats to either 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) or Aroclor 1254 results in female-selective induction of hepatic tumors. The relative potency of dioxins and polychlorinated biphenyl mixtures, such as Aroclor 1254, is often estimated using the internationally endorsed toxic equivalency (TEQ) approach. Comparing the genome wide changes in gene expression in both genders following exposure to TEQ doses of these chemicals should identify critical sets of early resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…This reduced sensitivity is partially explained by the human AhR having a tenfold reduced binding affinity to TCDD than rats (Connor and Aylward 2006). Primary hepatocyte studies corroborate this viewpoint and suggest even less human sensitivity relative to rats (Schrenk et al 1995; Silkworth et al 2008; Budinsky et al 2010; Carlson et al 2009; Black et al 2012; Le Vee et al 2010; Schrenk et al 1994). Much of the sensitivity comparison is based on CYP1A induction.…”
Section: Use Of In Vitro Systems For Predicting Liver Toxicitymentioning
confidence: 93%
See 1 more Smart Citation
“…This reduced sensitivity is partially explained by the human AhR having a tenfold reduced binding affinity to TCDD than rats (Connor and Aylward 2006). Primary hepatocyte studies corroborate this viewpoint and suggest even less human sensitivity relative to rats (Schrenk et al 1995; Silkworth et al 2008; Budinsky et al 2010; Carlson et al 2009; Black et al 2012; Le Vee et al 2010; Schrenk et al 1994). Much of the sensitivity comparison is based on CYP1A induction.…”
Section: Use Of In Vitro Systems For Predicting Liver Toxicitymentioning
confidence: 93%
“…Therefore, the TEFs do not reflect the relative potency comparison across the PCDD/F AhR ligands in humans, the range of variability and uncertainty in overall relative potency of a congener or the critical risk end point of cancer. Limited studies of CYP1A induction in primary human hepatocytes suggest that the TEF values are too conservative but again, CYP1A induction may not accurately depict the gene networks associated with the tumor promotion MOA (Budinsky et al 2010, 2012; Silkworth et al 2008). Genomic data for TCDD, 2,3,7,8-tetrachlorodibenzofuran (TCDF) and 2,3,4,7,8-pentachlorodibenzofuran (4-PeCDF) reveal that TCDF and 4-PeCDF are 27-fold and 35-fold less potent than TCDD (Rowlands et al 2011, 2012).…”
Section: Use Of In Vitro Systems For Predicting Liver Toxicitymentioning
confidence: 99%
“…But differences in sensitivities have also been identified within a single strain, between male and female animals (Pohjanvirta et al, 1993;Enan et al, 1996;Silkworth et al, 2008). In L-E rats, female animals are more sensitive to the acute lethality of TCDD (LD 50 = 9.8 μg/kg) while males are more resistant (LD 50 = 17.7 μg/kg) (Pohjanvirta et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In PMH, for example, we found an overlap of 22 genes between the gene sets induced by ARO and HCE. ARO was selected as AhR agonist (Table 2), but it is known that ARO in hepatocytes also binds to other nuclear receptors like the constitutive androstane receptor (CAR) and the pregnane X receptor (PXR) (Aly and Domenech 2009;Silkworth et al 2008). Kojima et al (2011) have shown that organochlorine pesticides HCE and HCH also act as PXR agonists.…”
Section: Discussionmentioning
confidence: 99%